The impact of work clothing design on workers’ comfort - Bragança, Sara (2015)
Physical and physiological comfort, at work and during leisure time, is important to human health and motivation. A growing number of jobs require workers to sit. Most clothes, except those intended for wheelchair users, were designed for walking or the standing position. Clothing designs should be user-oriented and meet users’ needs. Garment design should conform to body position and posture, not just shape and size. In this paper we present the ergometric impact of a new type of trousers designed to adapt to changes in position. Concentrations of compression forces, temperature and pressure were documented in an exploratory pilot study and contrasted to traditional designs. The new trousers showed significant decreases in compression force concentration, especially in and around the knees and waist. Most participants identified comfort as an important factor when purchasing a pair of trousers and that, for working purposes, they would prefer these special trousers rather than traditional designs.